Mechanisms, therapeutic implications, and methodological challenges of gut microbiota and cardiovascular diseases: a position paper by the ESC Working Group on Coronary Pathophysiology and Microcirculation - Tousoulis, Dimitris; Guzik, Tomasz; Padro, Teresa; Duncker, Dirk J; De Luca, Giuseppe; Eringa, Etto; Vavlukis, Marija; Antonopoulos, Alexios S; Katsimichas, Themistoklis; Cenko, Edina; Djordjevic-Dikic, Ana; Fleming, Ingrid; et al. (Oxford Journals, 2022)
The human gut microbiota is the microbial ecosystem in the small and large intestines of humans. It has been naturally preserved and evolved to play an important role in the function of the gastrointestinal tract and the physiology of its host, protecting from pathogen colonization, and participating in vitamin synthesis, the functions of the immune system, as well as glucose homeostasis and lipid metabolism, among others. Mounting evidence from animal and human studies indicates that the composition and metabolic profiles of the gut microbiota are linked to the pathogenesis of cardiovascular disease, particularly arterial hypertension, atherosclerosis, and heart failure. In this review article, we provide an overview of the function of the human gut microbiota, summarize, and critically address the evidence linking compositional and functional alterations of the gut microbiota with atherosclerosis and coronary artery disease and discuss the potential of strategies for therapeutically targeting the gut microbiota through various interventions.
Keywords: Atherosclerosis; Coronary artery disease; Gut microbiota; Short-chain fatty acids; Trimethylamine N-oxide